The Influence Of Lifestyle And Income On The Financial Behavior Of Generation Z In Makassar - Kurniatri Rumambo; Benyamin Mongan; Andryanus Paridy (LPPM Universitas Buddhi Dharma, 2025)
The increasing modernization and digitalization era have shaped the financial behavior of Generation Z, who are often more consumptive and find it challenging to manage their expenditures. This study aims to analyze the influence of lifestyle and income on the financial behavior of Generation Z who are currently working in Makassar. Using a quantitative approach, data were collected through an online questionnaire distributed to 40 respondents aged 15–27 years. The analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS software. The results indicate that lifestyle positively and significantly influences financial behavior, meaning that the more consumptive a person's lifestyle, the more it affects their financial decision-making. Additionally, income also has a positive and significant effect on financial behavior, implying that higher income allows for better financial management and decision-making. However, the coefficient of determination (R²) shows that lifestyle and income explain only 41.3% of the variance in financial behavior, suggesting that other external factors also play a role. These findings emphasize the importance of financial literacy education to help Generation Z develop healthier financial habits. Future research is recommended to explore other influencing factors, such as financial technology and psychological aspects, to gain a more comprehensive understanding of financial behavior among young professionals.